Study of quality of life and characteristic factors in women with breast cancer undergoing different types of therapy - Redhwan A. Al-Naggar, Muhamed T Osman, Nameer Al-Baghdadi (Journal of Applied Pharmaceutical Science, 2016)
Breast cancer is the most common cancer among women and an increasingly important issue is to evaluate quality of life (QoL) among these patients. The objective of this study was to appreciate the QoL and associated factors among breast cancer womenundergoing different types of therapy. A cross-sectional study was carried out among 166 breast cancer women from two specialized centres in Baghdad, Iraq, from February 2014 to December 2014. The questionnaire used in this study was “The Functional Assessment of Cancer Therapy-Breast (FACT-B)”. The majority were employee (60.3%), with high school education (63.2%), with no family history of cancer (79.5%). Majority were diagnosed with grade II (56.6%) and tumor size less than 2 cm in diameter (95.8%). The majority of women underwent mastectomy (98.2%), received chemotherapy, radiotherapy, and Tamoxifen therapy (89.8%, 29.5%, and 36.1%; respectively).The study found a significant difference between the quality of life among cancer patients and job, stage of cancer, size of tumor, and radiotherapy. Job, stage of cancer, size of tumor, and radiotherapy significantly influenced the women QoL. Therefore, more attention on these variables is highly recommended when dealing with breast cancer patients undergoing different types of therapy.
Keywords: Quality of Life (QoL), breast cancer, chemotherapy, radiotherapy.